2011
DOI: 10.5402/2011/108509
|View full text |Cite
|
Sign up to set email alerts
|

On the Spectrum of Threshold Graphs

Abstract: The antiregular connected graph onrvertices is defined as the connected graph whose vertex degrees take the values ofr−1distinct positive integers. We explore the spectrum of its adjacency matrix and show common properties with those of connected threshold graphs, having an equitable partition with a minimal numberrof parts. Structural and combinatorial properties can be deduced for related classes of graphs and in particular for the minimal configurations in the class of singular graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…In [19] it was proved that all eigenvalues of any threshold graph other than 0, 1 are main. However the analogous statement in the case of DNGs is not true.…”
Section: Main and Non-main Eigenvalues Of Dngsmentioning
confidence: 99%
“…In [19] it was proved that all eigenvalues of any threshold graph other than 0, 1 are main. However the analogous statement in the case of DNGs is not true.…”
Section: Main and Non-main Eigenvalues Of Dngsmentioning
confidence: 99%
“…As far as threshold graphs, spectral properties were studied by Sciriha and Farrugia in [14]. They showed that all eigenvalues, other than −1 or 0, are main.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral properties of co-graphs, which contain the class of threshold graphs, were studied in [2]. Threshold graphs were studied in [15,16] under the name nested split graphs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embora na prática, na maioria dos casos, issoé não trivial, pois não possuímos método algébrico para encontrar raízes de polinômios de grau maior do que 5, a classe de grafos threshold possui uma particularidade. Se Aé a matriz de adjacência de um grafo threshold G, o polinômio característico de G pode ser obtido através de uma redução da matriz A. Aqui será apresentado a idéia geral dessa redução, para mais detalhes, consultar [8]. Seja G um grafo threshold com sequência binária (…”
Section: Grafos Thresholdunclassified